Islam and the Plight of Modern Man - Hossein Nasr, Seyyed (Lahore Suhail Academy, 1999)
This is one of the most important writings of the author on the subject of the encounter and interrelation between Islam and modernism. Addressed at once to Muslims and Westerners, the author deals in depth with the intellectual and spiritual crisis of modern man as well as the dilemmas of the contemporary Muslim faced with the daunting challenge of the modern world. He charters a path for mutual understanding between Muslims and traditional elements of Western society as well as providing, on the basis of Islamic sapiental doctrines, criteria for judging various facets of modernism. The situation of Islam in the contemporary Muslim world is treated critically and in the postscript the author meditates upon the future of Islam and the Islamic world in light of the unprecedented challenges which the modern world poses for Muslims.
Include Bibliography and Index.
Keywords: Islam -- Interfaith relations -- Islam and secularism -- Christianity -- East and West -- Islam and world politics -- Theological anthropology--Islam -- Civilization, Western